THE MAIN FEATURES OF THE ORGANIZATION OF PROPER NUTRITION IN WOMEN DURING PREGNANCY - Kalandarova G.D. (Journal of new century innovations, 2024)
Annotation: Proper nutrition during pregnancy is vital for the health and development of both the mother and the growing fetus. This article explores the organization of proper nutrition for pregnant women, focusing on its importance, key considerations, and recommendations. It encompasses a literature analysis, methods employed in ensuring adequate nutrition, results obtained, discussion of findings, and concludes with suggestions for optimizing maternal and fetal health through nutrition during pregnancy.